EXPANDING THE SCOPE OF PSYCHOLOGICAL OPERATIONS IN THE GUERILLA WARFARE CONTEXT (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the significance of the moral factor in maintaining a high level of combat spirit in the armed forces.